PENINGKATAN KUALITAS PEMBELAJARAN PADA POKOK BAHASAN ANALISIS MOLEKUL MENGGUNAKAN INFRA MERAH (IR) DAN NUCLEAR MAGNETIK RESONANCE (NMR) MELALUI PEMANFAATAN PROGRAM HYPERCHEM DAN CHEMOFFICE - I Nyoman Candra; Nurhamidah (University of Bengkulu, 2023)
Final grades of student who participated in the Course of Instrumental Analytical Chemistry in Odd Semester, Academic Year of 2022/2023 indicate a low student achievement. The objective of this study was to improve the instruction of Instrumental Analytical Chemistry Course by increasing student learning activities and student achievement on the topic of infra red and nuclear magnetic resonance analysis by utilizing HyperChem and ChemOffice Software. Student and lecturer observation sheet were used for measuring student and lecturer activities, respectively while, an essay test sheet was given to measure student cognitive ability. Student and lecturer activity scores for Cycle 1 were 22 and 27, respectively and fell in “Good” category. Student activity score rose up to the maximum score, 27 while, lecturer activity score remained in maximum score in Cycle 2. Lecturer activity already had a maximum score in Cycle 1 because the lecturer was well-prepared in the instruction as well as successful implementation of learning plan. Increasing student achievement was also recorded from Cycle 1 (average 80.2) to Cycle 2 (average 88.5). The percentage of student who gained score above 65 was 93% in Cycle 1 and went up to 100% in Cycle 2. HyperChem and ChemDraw are able to assist the instruction of Instrumental Analytical Chemistry course on the topic of IR and NMR.